2006
DOI: 10.1111/j.1525-1438.2006.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17beta-estradiol and progesterone on transcription of human papillomavirus 16 E6/E7 oncogenes in CaSki and SiHa cell lines

Abstract: Several in vitro studies have addressed the interactions between estrogen/progesterone and human papillomavirus (HPV), but the results are controversial. We evaluated the effects of estrogen and progesterone and their antagonists on messenger RNA expression of HPV16 E6/E7 in HPV16-positive cell lines CaSki and SiHa with real-time reverse-transciptase polymerase chain reaction method. Colorimetric assay with tetrazolium salt (WST-1) and flow cytometry were used for testing proliferation and apoptosis. No statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Some evidence suggests a hormonal effect on oncogene expression, at least for HPV16 and 18, by action on progesterone/glucocorticoid-responsive elements in the long control region of the HPV genome (Cole and Danos, 1987;Gloss et al, 1989). However, more recent research has called such a mechanism into question (Ruutu et al, 2006), and would instead suggest hormonal effects impairing apoptosis of infected cells. Oral contraceptives and high parity are known risk factors for cervical cancer (Munoz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests a hormonal effect on oncogene expression, at least for HPV16 and 18, by action on progesterone/glucocorticoid-responsive elements in the long control region of the HPV genome (Cole and Danos, 1987;Gloss et al, 1989). However, more recent research has called such a mechanism into question (Ruutu et al, 2006), and would instead suggest hormonal effects impairing apoptosis of infected cells. Oral contraceptives and high parity are known risk factors for cervical cancer (Munoz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Both estrogen and progesterone have been shown to increase HPV replication and transcription, 18 thereby increasing viral load and making HPV easier to detect. Several studies have shown that it is difficult for most assays to detect low levels of HPV reliably.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study on HPV-16 positive CaSki and SiHa cells showed increased cell proliferation under the influence of oestrogen as well as progesterone but no change in HPV-16 E6/E7 transcription levels [50]. The authors suggested that the anti-apoptotic effect of oestrogen might allow a growth advantage for HPV infected cells [50]. In a model using luciferase reporter constructs under control of oestrogen response element promoter it was shown that HPV-16 E7 can dysregulate and reduce the function of steroid receptor coactivator 1, which may explain the role of steroid hormones as co-factors in the carcinogenesis of HR-HPV related disease [58].…”
Section: Hpv and Oestrogen In Cervical Carcinogenesismentioning
confidence: 93%
“…HPV oncogene expression may be increased in response to oestrogen and progesterone stimulation, thus causing cell growth [49,[51][52][53][54][55][56][57]. However, a study on HPV-16 positive CaSki and SiHa cells showed increased cell proliferation under the influence of oestrogen as well as progesterone but no change in HPV-16 E6/E7 transcription levels [50]. The authors suggested that the anti-apoptotic effect of oestrogen might allow a growth advantage for HPV infected cells [50].…”
Section: Hpv and Oestrogen In Cervical Carcinogenesismentioning
confidence: 96%
See 1 more Smart Citation